Allium leafminer (Diptera: Agromyzidae) host preference: implications for developing a trap cropping strategy - Lai, Pin-Chu; Sandhi, Ramandeep Kaur; Nault, Brian A. (Frontiers in Insect Science, 2023)
Allium leafminer (Phytomyza gymnostoma Loew) is an emerging invasive pest of Allium crops and has been threatening Allium crop production in the eastern United States since its introduction in 2015. Phytomyza gymnostoma can cause substantial economic loss in leek crops when late instars tunnel into the lower portion of the plant, which often renders the crop unmarketable. With limited management tools that are cost-effective and practical, especially for leeks produced in organic systems, we examined the attractiveness of other Allium crop species that might be considered in a trap cropping strategy. In 2021 and 2022, controlled environment choice tests and field trials were conducted to evaluate host preference of P. gymnostoma among Allium crop species including chives, scallion, an onion and scallion hybrid, and leek. Results from field trials indicated that only chives had more oviposition marks, cumulative numbers of eggs, and a higher density of P. gymnostoma larvae and pupae than leeks. We also assessed preference of P. gymnostoma for scallions that varied in size/age. Larger/older scallions had more oviposition marks and higher P. gymnostoma densities than smaller ones in controlled environment choice tests, but this size/age preference was not evident in field trials. Based on our findings, chives could be considered as a potential trap crop for minimizing P. gymnostoma damage in leek crops.